PENGARUH PENERAPAN PERMAINAN SUCKER BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP SEMEN PADANG TAHUN PELAJARAN 2013/2014 - Oktovani, Fauziah; Febriana, Rina; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was grounded by the studentsâ low achievement in mathematics at SMP Semen Padang. This research was aimed at revealing whether the mathematics conceptual understanding of the students taught by using Sucker Ball game was better than that of students taught by using conventional learning in class VIII of SMP Semen Padang. By using random sampling technique, class VIII.5 was chosen as the experimental class and class VIII.1 was chosen as the control one. The instrument of the research was an essay post-test whose reliability was 0,86. The data collected was analyzed by using normality test, homogeneity test and t-test. The result of data analysis showed that the average score of the students in the experimental class (70,15) was higher than those in the control class (50,06). Furthermore, the result of statistical test indicated that the value of tcalculated (5,8407) was bigger than ttable (1,645). Based on these results, it was concluded that the mathematics conceptual understanding of the students taught by using Sucker Ball game was better than that of students taught by using conventional learning in class VIII of SMP Semen Padang.